Sieben Stolpersteine jeglicher Schulreform: Ein Versuch über vernachlässigte Bedingtheiten (mathematica didactica, 2004)
As a critical sum up of more than 50 years engagement to teaching mathematics in elementary schools the article identifies seven major impediments that put every reform atrisk. These are in short: confusion of training and education (Ausbildung versus Bildung), narrowing of decision-maker’s perspective on reality through professional socialization, possible and factual role of master-teachers, increasing neglect of history, confidence in objectivity and power of scientific data, impotence of present teacher „education“, as well associetal acceptance of teachers and the qualities of student-teachers.